Mariamne face à l’absolutisme et la tyrannie : de la fin du XVIe siècle aux Femmes illustres ou les Harangues héroïques des Scudéry (1642) et à La Gallerie des femmes fortes de Le Moyne (1647) - Lisa Zeller (Etudes Epistémè)
The subject of Herod and Mariamne has enjoyed considerable success in France since the time of the Catholic League, in the context of the debate on the legitimacy of resistance to tyranny. Starting with the names and fates of Caussin’s and Tristan L’Hermite’s characters of Maria(m)ne as a possible allusion to the Jesuit Juan de Mariana, a defender of a political alternative to absolutism, silenced after the assassination of Henri IV, this article examines the representations of the character in two texts from the 1640s. In this context, this article proposes to read Mariamne’s speech in the Scudérys’ Femmes illustres as a fictional reconstruction of a buried historical perspective. Mariamne’s reflection on the image of herself circulated after her death, which elicits sympathy everywhere and horror at Herod’s tyranny, may thus be related to heroic opposition to Richelieu. If the harangue of Scudéry’s Mariamne represents the survival of alternative forms of collective memory and power, the reappearance of the character in Le Moyne’s Gallerie can in turn be understood in this context as part of a discursive strategy by which the Jesuit attempts to refute the accusations of a tyrannical usurpation of absolute power that had to justify the Parliament’s resistance to the regency of Anne of Austria and Mazarin. On the contrary, Anne appears as a reincarnation of the virtuous Mariamne, who thus becomes a figure legitimizing the regency, associated by Le Moyne with a classical republican vocabulary.